Vitamin D and LL-37 in Serum and Saliva: Insights into Oral Immunity - Sotiria Davidopoulou; Kali Makedou; Areti Kourti; Ioanna Gkeka; Panagiotis Karakostas; Maria Pikilidou; Kosmas Tolidis; Sotirios Kalfas (Current Issues in Molecular Biology)
(1) Background: In recent years, there has been a growing interest in understanding the innate immunity of the mouth, particularly the mechanisms through which vitamin D influences oral health. Researchers have increasingly focused on the association between vitamin D and the antimicrobial peptide LL-37 since the CAMP gene, responsible for encoding the LL-37 peptide, is a direct target of both vitamin D and its receptor (vitamin D receptor, VDR). This study aimed to explore the correlation between the 25-hydroxyvitamin D (25(OH)D) levels and the concentration of the LL-37 peptide in both serum and saliva. The objective was to compare the serum concentrations of 25(OH)D and ll-37 with those in saliva and to access the correlations between the two compounds. (2) Methods: Serum and whole saliva samples were collected from 72 healthy adults (mean age 28.68 ± 8.35). The levels of 25(OH)D and LL-37 were assessed in both the saliva and serum samples using commercially available enzyme-linked immunosorbent assay (ELISA) kits. (3) Results: The 25(OH)D levels in the serum (median 5.92 ng/mL, min–max 2.7–10.4 ng/mL) correlated with the LL-37 serum levels (62 ng/mL, min–max 18–378 ng/mL; Pearson’s r 0.328, p = 0.005). Additionally, the 25(OH)D levels in saliva (median 1.16 ng/mL, min–max 0.54–2.12 ng/mL) strongly correlated with the LL-37 salivary levels (median 44 ng/mL, min–max 6.5–205 ng/mL; Pearson’s r 0.667, p < 0.001). The 25(OH)D salivary levels demonstrated a robust correlation with the LL-37 salivary levels. (4) Conclusions: This discovery emphasizes the complex interplay between vitamin D and LL-37 and lay the groundwork for the further exploration of vitamin D’s role in oral immune function.